2021
DOI: 10.1007/s11553-021-00856-7
|View full text |Cite
|
Sign up to set email alerts
|

Mentalisieren und selbstregulative Fähigkeiten bei nichtklinischen Probanden

Abstract: Zusammenfassung Hintergrund Der Konfiguration selbstregulativer Fähigkeiten wird eine zentrale Rolle im Zustandekommen von Stress- und Belastungserleben zugewiesen, wobei dysfunktionale Anordnungen selbstregulativer Fähigkeiten charakteristisch für hohes Stresserleben sind. Mentalisieren – definiert als die Fähigkeit, Verhaltensweisen auf Basis mentaler Zustände wahrnehmen und bedenken zu können – ist ein ursprünglich klinisches Konzept, dem in jüngerer Zeit allerdings zusehends ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In line with this, Klusmann et al (2008) found that contextual factors such as school size, the size of taught courses, the school district, the socioeconomic status of students, and their cognitive abilities are only slightly associated with stress-related symptoms of exhaustion among teachers. Instead, research suggests that negative personal characteristics, such as maladaptive patterns of self-regulatory abilities (e.g., Schaarschmidt et al, 1999;Schwarzer et al, 2022a) are more strongly associated with higher stress experiences. For instance, Lehr et al (2008) found that teachers with negative patterns of coping strategies characterized by the tendency to resign report strong impairments in well-being, extensive emotional exhaustion, and higher depressive symptoms with overall large effect sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, Klusmann et al (2008) found that contextual factors such as school size, the size of taught courses, the school district, the socioeconomic status of students, and their cognitive abilities are only slightly associated with stress-related symptoms of exhaustion among teachers. Instead, research suggests that negative personal characteristics, such as maladaptive patterns of self-regulatory abilities (e.g., Schaarschmidt et al, 1999;Schwarzer et al, 2022a) are more strongly associated with higher stress experiences. For instance, Lehr et al (2008) found that teachers with negative patterns of coping strategies characterized by the tendency to resign report strong impairments in well-being, extensive emotional exhaustion, and higher depressive symptoms with overall large effect sizes.…”
Section: Introductionmentioning
confidence: 99%